Kebutuhan Pengembangan Media Audio Visual Pokok Bahasan Sintesis Protein Untuk SMA - Ima Nurani; Muh. Amir Masruhim; Evie Palenewen (Jurnal Pendidikan Sains, 2016)
Abstract: The aim of this study is to obtain 1) description of the use of learning media as teaching resource on biology learning process that has been happening in the field, 2) the views and constraints faced by teachers in the field for delivering protein synthesis subject, 3) formulation of learning media that needs to be developed on biology learning of protein synthesis subject. The observation result from teacher’s needs assessment that analyzed using descriptive qualitative indicated that 1) the use of learning media as teaching resource on biology learning process has not done optimally. There are constraints in delivery of material, especially abstract material, 2) the protein synthesis subject is a difficult subject, in its delivery, teachers need media that can visualize the process of protein synthesis for twelfth grade and explain it in detail and correctly so there is no misconception of students towards protein synthesis subject, and 3) the learning media that needs to be developed in biology learning of protein synthesis subject is in the form of audio-visual media.Key Words: needs assessment, media, audiovisual, protein synthesisAbstrak: Tujuan penelitian ini adalah untuk memperoleh 1) gambaran penggunaan media pembelajaran sebagai sumber ajar pada proses pembelajaran biologi yang selama ini terjadi di lapangan, 2) pandangan dan kendala yang dihadapi para guru di lapangan terhadap penyampaian pokok bahasan sintesis protein, 3) rumusan media pembelajaran yang perlu dikembangkan dalam pembelajaran biologi pokok bahasan sintesis protein. Hasil observasi kebutuhan guru yang dianalisis secara deskriptif kualitatif menunjukkan bahwa 1) penggunaan media pembelajaran sebagai sumber ajar pada proses pembelajaran biologi selama ini belum dilakukan secara maksimal. Terdapat kendala penyampaian materi terutama materi yang bersifat abstrak, 2) pokok bahasan sintesis protein merupakan materi yang sulit. Dalam penyampaiannya, guru membutuhkan media yang dapat memvisualisasikan proses dan menjelaskannya secara detail dan benar sehingga tidak terjadi miskonsepsi siswa terhadap pokok bahasan sintesis protein, dan 3) media pembelajaran yang perlu dikembangkan dalam pembelajaran biologi pokok bahasan sintesis protein adalah berupa media audio visual.Kata kunci: analisis kebutuhan, media, audiovisual, sintesis protein